Formwork with Variable Geometry for Concrete Shells Production Technology (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
One of the main constructive materials in the building sphere is a precast concrete and fiber concrete. It is well influenced by scientific research basis, development and implementation of progressive technologies. The fiber concrete it is an ideal material with practically unlimited number of shapes. A nomenclature of concrete articles increases, it is working on different shape formation and processing. While preparation for this document started with the concept fabrication, it is necessary to understand the methods of construction variable geometry formwork of concrete thin-shell surfaces, both past and present as a point of departure. An understanding of this background helps provide an essential foundation for the exploration of new potential advances in the field of thin-shell construction. Obviously that is the reason for fiber concrete to be the most widespread constructive building material all over the world. In the article are considered shell development technology features and is evaluated technical and economical effectiveness of concrete shells with thin walls. Now variable geometry systems from flexible materials are developing and improving, there is a great potential followed by modern events in concrete technology. The results of laboratory experiments have proved that the technology can be used for fibro concrete shell production and construction.